Pre-Pottery Neolithic A Settlement Variability: Evidence for Sociopolitical Developments in the Southern Levant - Kuijit, Ian (Journal of Mediterranean Archaeology, 1994)
Despite considerable archaeological research, it is only since the mid-1980s that sites dating to the foraging/farming transition, generally known as the Pre-Pottery Neolithic A period (PPNA) (ca. 10,500/10,300 - 9,300 BP), have been identified in Jordan. This under-representation of PPNA sites in the archaeological record is both a function of the relative archaeological visibility of PPNA material culture compared to that of other periods (including the type of architectural remains, small site size, and the largely non-diagnostic character of PPNA chipped stone assemblages, and the specific historical conditions of field surveys. After reviewing recent research on known PPNA sites, I argue that site location, physical area, architecture, and relative access to trade goods among PPNA communities in the Levant illustrate the existence of a regional site hierarchy, epitomized by large Jordan valley agricultural villages and smaller satellite communities situated in adjacent environmental areas.